From barriers to opportunities: Enabling investments in resource efficiency for sustainable development (Public Sector Economics - submission site, 2019)
Increasing investments in resource efficiency is considered essential for transitioning towards a sustainable model of economic growth. This article presents evidence on the complex incentives, trade-offs, and challenges associated with the economics and politics of resource efficiency investments, especially in light of the Sustainable Development Goals and the Paris Climate Agreement. By synthesising and evaluating a wide range of empirical evidence, practitioners’ insights, and policy perspectives, this article carefully examines the role of resource efficiency in reconciling environmental and economic objectives. It makes particular reference to the investment barriers and transitional implications of moving economies towards more circular and resource efficient pathways. In doing so, it provides a policy-oriented guide and toolbox to help overcome barriers, unlock the economic potential of resource efficiency, and highlight the challenges associated with the resource transition. Overall, this article brings together evidence, aiming to further develop and propose new strategies for improving the efficient use of natural resources to advance the sustainable development agenda.